Peningkatan Pelayanan Kepuasan Pelanggan Melalui Pelatihan Service Excellent Di PT Prima Karya Sarana Sejahtera Palembang - Dwi Hurriyati; Nadila (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
One of the biggest challenges in business in the global era is creating and maintaining satisfied and loyal customers. It is difficult for a company to survive in the long term without satisfied customers. Every company in the field of products and services has a different excellent service system. This research is aimed at finding out how efficient it is in helping the Excellent Service process. The methods used in the research are questionnaires, documentation and using the Androgogy development model. The results of this research show that there is efficiency in Service Excellent training, meaning that the learning process has demonstrated an understanding of the material. This is in line with the opinion of Edwin B. Flippo (Sukma, H.P 2018) that after employees are recruited, selected and appointed/introduced, they must then be developed to be more suited to the job and organization. This development includes training to increase general knowledge and understanding of the entire environment. Meanwhile, based on the assessment of superiors and subordinates, in this case the Service Excellent Training participants, changes in employee behavior after attending the training show that employees have experienced an increase in their behavior of helping others, self-integrity, mutual respect, professionalism at work, working together in teams, completing tasks on time, caring about colleagues and customers, and using greetings to colleagues, superiors and customers. The results of this assessment mean that the training carried out has had a positive effect on improving the behavior expected by the organization and it can be said that the training held has been effective.